Colchicine to Reduce Atrial Fibrillation in the Postoperative Period of Myocardial Revascularization - Zarpelon,Camila Stuchi (2016)
Abstract Background: The high prevalence of atrial fibrillation (AF) in the postoperative period of myocardial revascularization surgery increases morbidity and mortality. Objective: To assess the efficacy of colchicine to prevent AF in the postoperative period of myocardial revascularization surgery, the impact of AF on hospital length of stay and death, and to identify its risk factors. Methods: Between May 2012 and November 2013, 140 patients submitted to myocardial revascularization surgery were randomized, 69 to the control group and 71 to the colchicine group. Colchicine was used at the dose of 1 mg orally, twice daily, preoperatively, and of 0.5 mg, twice daily, until hospital discharge. A single dose of 1 mg was administered to those admitted 12 hours or less before surgery. Results: The primary endpoint was AF rate in the postoperative period of myocardial revascularization surgery. Colchicine group patients showed no reduction in AF incidence as compared to control group patients (7.04% versus 13.04%, respectively; p = 0.271). There was no statistically significant difference between the groups regarding death from any cause rate (5.6% versus 10.1%; p = 0,363) and hospital length of stay (14.5 ± 11.5 versus 13.3 ± 9.4 days; p = 0.490). However, colchicine group patients had a higher infection rate (26.8% versus 8.7%; p = 0.007). Conclusion: The use of colchicine to prevent AF after myocardial revascularization surgery was not effective in the present study. Brazilian Registry of Clinical Trials number RBR-556dhr.